2007
DOI: 10.1007/s00432-007-0334-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of all-trans retinoic acid for treating adult T cell leukemia

Abstract: These results indicated that ATRA might be a useful agent for the safe treatment of ATL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…94 Treatment results for 20 patients with ATL were recently reported. 95 The efficacy of ATRA was as follows : 2 PR, 2 no change (NC), 3 progressive disease (PD) in 7 acute type ATL, 3 PR in 3 lymphoma type ATL, 1 PR, 3 NC in 4 chronic type ATL, and 2 PR, 4 NC in 6 smoldering type ATL. These data suggest that retinoids are effective, but have limited efficacy.…”
Section: ) Retinoid Derivativesmentioning
confidence: 99%
“…94 Treatment results for 20 patients with ATL were recently reported. 95 The efficacy of ATRA was as follows : 2 PR, 2 no change (NC), 3 progressive disease (PD) in 7 acute type ATL, 3 PR in 3 lymphoma type ATL, 1 PR, 3 NC in 4 chronic type ATL, and 2 PR, 4 NC in 6 smoldering type ATL. These data suggest that retinoids are effective, but have limited efficacy.…”
Section: ) Retinoid Derivativesmentioning
confidence: 99%
“…18 Finally, ATRA was clinically evaluated in 20 ATL patients and showed no complete remission but a partial response in 40% of the patients. 19 Even though natural retinoids have been used in APL treatment, their broad clinical use has been hampered by side effects and resistance. In addition, retinoid receptor signaling pathway is deregulated in several cancers, making tumor cells resistant to natural retinoids.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Thus, synthetic retinoids were developed with increased specificity and decreased toxicity. One promising compound is the synthetic adamantly retinoid, ST1926 (2E)-3-[39-(1-adamantyl)-49-hydroxy [1,19-biphenyl]-4-yl]-2-propenoic acid, an analog of CD437 6-[3-(1-adamantyl)-4-hydroxyphenyl]-2-naphthalene carboxylic acid. 22 ST1926 showed potential efficacy in solid tumors and hematological malignancies with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, clinical responses to retinoids have been reported in various T-cell malignancies, including PTCL, CTCL, and adult T-cell leukemia (ATL) [912, 1922]. For example, Cheng et al reported 5 complete responses and one partial response among 12 PTCL patients treated with 13-cis retinoic acids [12].…”
Section: Discussionmentioning
confidence: 99%